Belajar Sambil Bermain Origami Di MIS Babakan, Ciamis - nugraha, Ilham; Juliyana, Ilham; Muhamad Akbar, Adiansyah; Andang Permana, Asep; Andrian, Bagas; Ibrahim, Bobi; Nur Zaidan, Rafi Hanif; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Play is an activity that is inseparable from children. This circumstance has captivated researchers since the 17th century to conduct studies on children and play. Researchers aim to demonstrate the extent to which play influences children, whether it is merely for seeking social recognition and acceptance or just to fill leisure time. Objective: The community service activity conducted aims to enhance the learning creativity of school-age children by combining counseling approaches and origami crafting activities as a means of playful learning. Method: This community service employs the counseling method by directly teaching origami assembly techniques to 12 students at MIS Babakan, Baregbeg District, Ciamis Regency, West Java. Result: In the pretest phase, 83.33% of the 12 children exhibited a lack of creativity development, while only 16.67% showed good creativity development. It is emphasized that counseling on origami assembly is considered a crucial step, and the post-test results indicate improvement, with only 8.33% of children showing a lack of creativity development, while 91.67% achieved a good level of creativity development. Conclussion: This Community Service activity has proven to be highly successful overall, receiving positive responses and resulting in a significant improvement in creativity development after the counseling on learning through playing origami assembly. Introduction: Play is an activity that is inseparable from children. This circumstance has captivated researchers since the 17th century to conduct studies on children and play. Researchers aim to demonstrate the extent to which play influences children, whether it is merely for seeking social recognition and acceptance or just to fill leisure time. Objective: The community service activity conducted aims to enhance the learning creativity of school-age children by combining counseling approaches and origami crafting activities as a means of playful learning. Method: This community service employs the counseling method by directly teaching origami assembly techniques to 12 students at MIS Babakan, Baregbeg District, Ciamis Regency, West Java. Result: In the pretest phase, 83.33% of the 12 children exhibited a lack of creativity development, while only 16.67% showed good creativity development. It is emphasized that counseling on origami assembly is considered a crucial step, and the post-test results indicate improvement, with only 8.33% of children showing a lack of creativity development, while 91.67% achieved a good level of creativity development. Conclussion: This Community Service activity has proven to be highly successful overall, receiving positive responses and resulting in a significant improvement in creativity development after the counseling on learning through playing origami assembly.